Legal support for the use of natural therapeutic resources in sanatorium and resort treatment of the population - Kostytsky, V. V.; Sydor, V. D.; Kostytska, I. O. (Zaporozhye Medical Journal, 2019)
The aim. To conduct a comprehensive study of the legal regulation peculiarities of natural therapeutic resources and factors of sanatorium and resort treatment for the population, to identify problems of legal regulation of these relations and to outline the ways to resolve them. Materials and methods. The research material is a modern regulatory framework. The methods of information retrieval, analysis, systematization and generalization were carried out. Results. It has been established that natural therapeutic resources include mineral and thermal water, medical mud and ozokerite, sea and lake brine, sea water, natural objects and complexes with favorable climatic conditions. It has been substantiated that sanatorium and spa treatment is an important part that provides continuity and complexity of medical rehabilitation measures. The main resorts, located on theterritory ofUkraine, have been described. It has been determined that regulation of social relations in the sphere of organization and development of resorts and sanatorium-resort treatment, detection and accounting of natural medical resources, ensuring their rational extraction, use and protection in order to create favorable conditions for treatment, medical rehabilitation, prevention of diseases and vacation for people is provided by environmental, land, health care and resort legislation. Conclusions. Legal regulation of the natural therapeutic resources usage is ensured by environmental, land, health care and resort legislation. The purpose of this legislation is to regulate social relations in the sphere of organization and development of resorts and sanatorium and spa treatment, to detect and account natural medical resources, to ensure their rational extraction, use and protection in order to create favorable conditions for treatment, medical rehabilitation, prevention of diseases and population health improvement. Efficient exploitation of natural therapeutic resources in resort treatment is currently affected by a number of economic, political, environmental problems, which have to be solved by organizational and legal means of the state impact on such legal relations.